Scientific Determination Of The Antimicrobial Properties Of Tithonia Diversifolia Stem, Bark, Leaf And Root Bark Extracts On Prevention And Control Of Diarrhea. - Kihika, Joseph Kanyi (Journal of Pharmaceutical Research and Opinion, 2014)
The World Health Organization (WHO) estimates that 4 billion people, 80% of the world population, presently use herbal medicine for some aspect of primary health care. WHO also estimates that the global market for herbal medicines is worth more than US60 billion per year. This is because it is either cheaper and accessible or more culturally appropriate. Herbal medicine is a major component in all indigenous peoples’ traditional medicine and a common element in Ayurvedic, homeopathic, naturopathic, traditional oriental, and Native American Indian medicine. WHO notes that of 119 plant-derived pharmaceutical medicines, about 74% are used in modern medicine in ways that correlated directly with their traditional uses as plant medicines by native cultures. Major pharmaceutical companies are currently conducting extensive research on plant materials gathered from the rain forests and other places for their potential medicinal value ( WHO, 2003).